PENGARUH KEPEMILIKAN ASING DAN DEBT COVENANT TERHADAP KEPUTUSAN MELAKUKAN TRANSFER PRICING DENGAN BEBAN PAJAK SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2019-2023) - Fidiantoro, Aldi Agung; Eliza, Any; Ermawati, Liya (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the effect of foreign ownership and debt covenants on transfer pricing decisions with tax burden as a moderating variable. Transfer pricing is a policy carried out by a company to transfer part of the wealth of a company to an affiliated company located abroad that has a lower tax rate. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange in the 2019-2023 period. The sample selection was carried out through purposive sampling technique where a total sample of 24 companies was obtained, with a total observation data of 120 data. This study uses descriptive statistical tests, classical assumption tests, hypothesis tests and moderated regression analysis (MRA). The results showed that foreign ownership and debt covenant have a positive effect on transfer pricing decisions. The results also show that the tax burden is able to moderate the influence of foreign ownership on transfer pricing decisions, but not able to moderate the influence of debt covenants on transfer pricing decisions.